2020
DOI: 10.1038/s41467-020-17875-1
|View full text |Cite
|
Sign up to set email alerts
|

Within-individual phenotypic plasticity in flowers fosters pollination niche shift

Abstract: Phenotypic plasticity, the ability of a genotype of producing different phenotypes when exposed to different environments, may impact ecological interactions. We study here how within-individual plasticity in Moricandia arvensis flowers modifies its pollination niche. During spring, this plant produces large, cross-shaped, UV-reflecting lilac flowers attracting mostly long-tongued large bees. However, unlike most co-occurring species, M. arvensis keeps flowering during the hot, dry summer due to its plasticity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
53
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 86 publications
0
53
0
3
Order By: Relevance
“…Within-generational plasticity in flower color as well as the role of epigenetic inheritance in flower color variation have been recently reported ( Gómez et al, 2020 ; Han et al, 2020 ). However, little work has focused on the possible transgenerational nature of plasticity in flower color and its potential eco-evolutionary causes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Within-generational plasticity in flower color as well as the role of epigenetic inheritance in flower color variation have been recently reported ( Gómez et al, 2020 ; Han et al, 2020 ). However, little work has focused on the possible transgenerational nature of plasticity in flower color and its potential eco-evolutionary causes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, flower color polymorphism is expected to involve changes in nucleotide sequence that are transmitted to subsequent generations. Recently, it has been found that a radical change in flower morphology, including petal color, in Moricandia arvensis is due to within-individual plasticity produced by seasonal changes in climatic conditions ( Gómez et al, 2020 ). A transcriptomic analysis found a coordinated response of more than 600 genes that was differentially expressed between two types of flowers suggesting a genetic basis for this plastic response ( Gómez et al, 2020 ; see also Laitinen and Nikoloski, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flower color transitions are common between related species ( Zufall and Rausher, 2004 ; Tripp and Manos, 2008 ; Streisfeld and Rausher, 2009 ; Smith and Rausher, 2011 ; Wessinger and Rausher, 2013 ; Roberts and Roalson, 2017 ). However, some lineages exhibit striking flower color variation within species ( Gigord et al, 2001 ; Schemske and Bierzychudek, 2007 ; Gómez et al, 2020 ). Flower color polymorphisms, the coexistence of two or more discrete flower color phenotypes within a population ( Huxley, 1955 ; Schemske and Bierzychudek, 2007 ), is relatively common and concentrated in some families of angiosperms ( Narbona et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…While some authors postulate that pigment production, specifically anthocyanins, can be expensive due to associated costs of some metabolic reactions such as glycosylation or acetylation (Chalker-Scott, 2002;Steyn et al, 2002), others have argued that the cost might in fact be low (Tanaka et al, 2008). It is also worth noting that anthocyanins provide colouration even at very low concentrations (van der Kooi et al, 2019;Narbona, unpublished data), and that this colouration is conspicuous to pollinators and can affect their behaviour (Papiorek et al, 2013) or even the attraction to certain groups (Gómez et al, 2020). Even if the direct cost of producing floral pigment is low, the production of more greatly coloured flowers might incur an additional indirect cost of higher herbivory damage if it is associated with easier detection by herbivores (Strauss and Whittall, 2006).…”
Section: Discussionmentioning
confidence: 99%